Effects of prehabilitation and rehabilitation including a home-based component on physical fitness, adherence, treatment tolerance, and recovery in patients with non-small cell lung cancer: A systematic review. (June 2017) - Driessen, Elisabeth J.; Peeters, Marieke E.; Bongers, Bart C.; Maas, Huub A.; Bootsma, Gerbern P.; van Meeteren, Nico L.; Janssen-Heijnen, Maryska L.
Abstract: This systematic review aimed to examine physical fitness, adherence, treatment tolerance, and recovery for (p)rehabilitation including a home-based component for patients with non-small cell lung cancer (NSCLC). PRISMA and Cochrane guidelines were followed. Studies describing (home-based) prehabilitation or rehabilitation in patients with NSCLC were included from four databases (January 2000–April 2016, N  = 11). Nine of ten rehabilitation studies and one prehabilitation study (437 NSCLC patients, mean age 59–72 years) showed significantly or clinically relevant improved physical fitness. Three (27%) assessed home-based training and eight (73%) combined training at home, inhospital (intramural) and/or at the physiotherapy practice/department (extramural). Six (55%) applied supervision of home-based components, and four (36%) a personalized training program. Adherence varied strongly (9–125% for exercises, 50–100% for patients). Treatment tolerance and recovery were heterogeneously reported. Although promising results of (p)rehabilitation for improving physical fitness were found (especially in case of supervision and personalization), adequately powered studies for home-based (p)rehabilitation are needed.